A survey of security issues in multicast communications. - Moyer, M.J (IEEE Network : the magazine of global information exchange)
The emergence and popularity of group-oriented applications on the World Wide Web has triggered a demand for scalable security solutions for group communication. One such solution, secure multicast is appealing because it leverages the efficiency of multicast data delivery. However, it also presents several research challenges, most notably in a group communication architecture, group key management, and message source authentication. In this survey, we discuss these issues and review proposed solutions to them